Physician moral injury in the context of moral, ethical and legal codes - Day, Philip (Journal of medical ethics, 2022)
After 40 years of attributing high rates of physician career dissatisfaction, attrition, alcoholism, divorce and suicide to ‘burnout’, there is growing recognition that these outcomes may instead be caused by moral injury. This has led to a debate about the relative diagnostic merits of these two terms, a recognition that interventions designed to treat burnout may be ineffective, and much perplexity about how—if at all—this changes anything. The current research seeks to develop the construct of moral injury outside military contexts, generate more robust validity tests and more fully describe and measure the experiences of persons exposed to moral harms. Absent from the literature is a mechanism through which to move from the collective moral injury experience of physicians to a systematic change in the structure of medical practice. To address this, after providing a brief history, definitions and contrasts between burnout, moral distress and moral injury, we review the interplay of moral and ethical codes in the context of moral injury. We conclude by suggesting that professional associations can potentially prevent moral injury by providing protections for physicians within their codes of ethics.